2006
DOI: 10.1111/j.1365-3164.2005.00495.x
|View full text |Cite
|
Sign up to set email alerts
|

Dermatitis in a dog induced by Straelensia cynotis: a case report and review of the literature

Abstract: This case report describes a highly pruritic, papular and crusted dermatitis affecting the dorsum of a dog and microscopically diagnosed as dermatitis induced by Straelensia cynotis. Histologically, each papule was characterized by a dilated hair follicle with marked pseudoepitheliomatous hyperplasia, perifollicular mucinosis and an abundant mononuclear infiltration by plasma and mast cells. Each dilated follicle contained a larval mite. A therapy including systemic ivermectins and oral antibiotic therapy was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
18
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 8 publications
10
18
0
Order By: Relevance
“…The pathognomonic histopathological features of straelensiosis, including pseudoepitheliomatous follicular hyperplasia and abundant perifollicular mucinosis (Le Net et al 2002, Seixas et al 2006, Ramirez et al 2009) were noted in the present cases. A blood-packed mass of irregular squamous epithelial cells with surrounding tissue neovascularisation was noted in one case.…”
Section: Straelensiosis In Cats and Dogs In Israelsupporting
confidence: 59%
See 2 more Smart Citations
“…The pathognomonic histopathological features of straelensiosis, including pseudoepitheliomatous follicular hyperplasia and abundant perifollicular mucinosis (Le Net et al 2002, Seixas et al 2006, Ramirez et al 2009) were noted in the present cases. A blood-packed mass of irregular squamous epithelial cells with surrounding tissue neovascularisation was noted in one case.…”
Section: Straelensiosis In Cats and Dogs In Israelsupporting
confidence: 59%
“…Albeit, it is noteworthy that other investigators proposed that remission of clinical signs occurs regardless of the treatment protocol, corresponding to the larva detaching from the stylostome upon completion of feeding (Fain and Le Net , Seixas et al . ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The mites attach themselves to the skin and make a stylostome, a channel through which salivary enzymes are injected and digested tissue fluids are withdrawn (Ginn et al 2007). Although lesions associated with trombiculid mite infestations are usually mild, some authors reported grossly apparent skin lesions in wild and domestic mammals (Lowenstine et al 1979;O'Callaghan et al 1994;Little et al 1997;Cunningham et al 2001;Seixas et al 2006). We report a case of dermatitis caused by trombiculid mite infestation in an Amami rabbit (Pentalagus furnessi), an endangered leporid that lives only on two islands (Amami-Oshima Island and Tokunoshima Island) of the Ryukyu Archipelago, Japan.…”
mentioning
confidence: 82%
“…3 Seixas et al . 1 suggested that the pruritus was due to the severe perifollicular infiltration of mast cells, and they did not rule out a secondary bacterial infection. In contrast to Le Net et al .…”
Section: Straelensiosis In a Dog In Spainmentioning
confidence: 99%